Acid hydrolysis of hemicellulose from oil palm frond / Nurhasmira Che Azmi - Che Azmi, Nurhasmira (2010)
Hydrolysis of hemicellulose from oil palm frond was studied in order to determine the optimal condition for the hydrolysis. In this study, hemicellulose was extracted using 3 M potassium hydroxide solution. In order to determine the optimal condition of hydrolysis, hemicellulose was then hydrolysed at different time (0, 20, 40, 80 min), different hemicellulose concentration (0.5%, 1.0%, 2.0%) and different acid concentration (0.05 M, 0.1 M, 0.2 M). The hydrolysates were analyzed for reducing sugar concentration by using UV-Vis spectrophotometer. The hemicellulose yield was 24.6% which is high content of hemicellulose makes this waste adequate for acid hydrolysis. The optimal condition was 2% of hemicellulose with 0.05 M H2SO4 at 40 min. The longer reaction times and higher concentration of acid led to decreased oligosaccharide production and enhanced concentrations of monosaccharide. Each of the optimal condition obtained the highest reducing sugar concentration which indicates the production of oligosaccharide.